Environmental performance of glass foam as insulation material from waste glass with the alkali activation process - Anna Mazzi; Michela Sciarrone; Enrico Bernardo (Heliyon, 2023)
Glass foams is an interesting option for the use of fractions of glass cullet otherwise destined to landfills. As building insulation materials, glass foams obtained by conventional processes have still some drawbacks in the purity of starting feedstock, which can be avoided by implementing an alkali activation process. Using the life cycle assessment methodology, the research analyses the potential impacts associated to the glass foam obtained from waste glass through the alkali activation in a laboratory scale plant with ‘cradle to grave’ perspective. The main phases included in the system boundaries are the downstream activities related to the transportation of glass waste and avoided landfill disposal, the production process to obtain the glass foam, and the upstream activities related to the transportation to potential use phase and the end of life. The life cycle environmental profile of glass foam is calculated starting from primary data integrated with the Ecoinvent database, and using the ReCiPe 2016 impact assessment method and the SimaPro software. Results demonstrate the greatest contribution on the overall environmental impacts due to the production, in which the main impacts are linked to electricity consumption for drying and firing and surfactant for the foaming. Sensitivity analyses clarify that consistent improvement in overall environmental impacts can be obtain with minimization of distances both between glass waste and production site, and between glass foam production and use; otherwise, different energy-mix and lower temperature in chemical processes have negligible effects in the environmental profile. The research reveals useful information to optimize the upcycling of glass foam production before moving on the industrialization: future investigations should involve the selection of biodegradable surfactants, from renewable sources.